2015
DOI: 10.1155/2015/410979
|View full text |Cite
|
Sign up to set email alerts
|

Classic and Modern Meridian Studies: A Review of Low Hydraulic Resistance Channels along Meridians and Their Relevance for Therapeutic Effects in Traditional Chinese Medicine

Abstract: Meridian theory is one of the core components of the theory of traditional Chinese medicine (TCM). It gives an integral explanation for how human life works, how a disease forms, and how a therapy acts to treat a disease. If we do not understand the meridians, it is hard to understand the TCM. People in China and abroad had been working hard for 50 years, trying to understand the meridians; then 15 years ago a breakthrough idea appeared when we realized that they are low resistance fluid channels where various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 37 publications
(41 reference statements)
0
40
0
2
Order By: Relevance
“…Previous studies have shown that acupoint areas are enriched in nerve endings, blood vessels, and mast cells, and these components constitute the basic structure of axon reflex [ 6 8 ]. When an Acup point was stimulated, axonal reflex was aroused; then the Acup signal was amplified and transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that acupoint areas are enriched in nerve endings, blood vessels, and mast cells, and these components constitute the basic structure of axon reflex [ 6 8 ]. When an Acup point was stimulated, axonal reflex was aroused; then the Acup signal was amplified and transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…The natural compounds extracted by TCM have been widely used to treat a number of diseases (11). Researchers have studied structural modification and artificial synthesis using the natural structure as a template to investigate the structure of these compounds (12).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine pays attention to channel tropism, which refers to the close relationship between drug action and human meridians and collaterals, in order to show the selectivity of a drug action on a certain part of the human body [36].…”
Section: Active Compounds Analysismentioning
confidence: 99%